(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the utilization and impact of the Indonesia Smart College Card (KIP-K) funds on improving student achievement at the YAPAN Surabaya College of Economics. The study used a quantitative approach with a sample of 57 students determined using the Slovin formula. Data were collected through direct questionnaires distributed to KIP-K recipient students and analyzed using multiple linear regression with the help of IBM SPSS Statistics. The research instrument was first tested for validity and reliability to ensure the validity of the data. The results show that the utilization of KIP-K living cost scholarship funds and the perceived impact of receiving these funds have a positive and significant effect on improving student achievement, both partially and simultaneously. This finding indicates that KIP-K funds have been utilized effectively to support students’ academic needs and study continuity, thus contributing to improved learning achievement. The results also show that the assumption regarding the suboptimal utilization of scholarship funds by KIP-K recipient students is not proven. Thus, the KIP-K program has been proven to provide real benefits in supporting student academic success at private universities